Relationship of Information Sources with Knowledge Levels of Nutrition in Pregnant Women in Ciruas Health Center - Albahra, Albahra; Setiawan, Memed Sena; Fathiyati, Fathiyati (Akademi Keperawatan RSPAD Gatot Soebroto, 2021)
The purpose of this study was to determine the relationship between sources of information and the level of knowledge about nutrition in pregnant women at the Ciruas Health Center in 2019, including family information, mass media information, and information on health workers. This type of research is analytic, with a cross sectional design (cross-sectional). Data analysis with univariate analysis (frequency distribution) and bivariate analysis (Kai Squared Test). Based on the results of the study, it was found that most of the mothers obtained good sources of information from their families (62.7%). Statistical test results obtained p value = 0.031 and OR = 4.821, indicating that there is a significant relationship between family sources of information and the level of knowledge about nutrition in pregnant women, most of the mothers received good sources of information from health workers (58.8%). Statistical test results obtained p value = 0.041 and OR = 4.185, so that there is a significant relationship between sources of information from health workers and the level of knowledge about nutrition in pregnant women and most mothers get good sources of information from the mass media (84.3%). The results of statistical tests obtained p value = 0.117 and OR = 6.682, so there is no significant relationship between sources of mass media information and the level of knowledge about nutrition in pregnant women